2017
DOI: 10.1186/s12882-017-0647-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mycophenolate mofetil in patients with IgA nephropathy: an update meta-analysis

Abstract: BackgroundThe application of mycophenolate mofetil (MMF) in treating patients with immunoglobulin A nephropathy (IgAN) remains uncertain. This update meta-analysis was performed to re-evaluate the therapeutic potential of MMF in IgAN.MethodsArticles were obtained by searching the electronic databases without language restriction. Randomized controlled trials studying the role of MMF in treating IgAN were collected. The quality of included studies was critically evaluated. Data analyses were performed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…First, the number of observed events is small and limits the statistical power of this explorative study to a certain extent. However, according to a recent meta-analysis, eight randomized controlled trials have assessed the use of MMF in patients with IgA nephropathy (11,12,(28)(29)(30)(31)33,49,50). Most of them were also small-sized and the study with the biggest size included 84 patients (33).…”
Section: Resultsmentioning
confidence: 99%
“…First, the number of observed events is small and limits the statistical power of this explorative study to a certain extent. However, according to a recent meta-analysis, eight randomized controlled trials have assessed the use of MMF in patients with IgA nephropathy (11,12,(28)(29)(30)(31)33,49,50). Most of them were also small-sized and the study with the biggest size included 84 patients (33).…”
Section: Resultsmentioning
confidence: 99%
“…Despite MMF was first used to treat IgAN in 1997, 8 some meta-analysis shows the efficacy of MMF in IgAN. 9 To date, the four published randomized controlled trials from China and western countries have shown different clinical profile in patients with IgAN. 10 Clinically, renal histologic features should not be considered a criterion for excluding patients from active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent randomized, double‐blind, placebo‐controlled trial, 44 patients from North America with IgAN was stopped prematurely due to lack of observed benefit . Putting these results together in a meta‐analysis, it was therefore not surprising that MMF was demonstrated to be of benefit in Asians but not Caucasians . In a recent study, 176 Chinese IgAN patients with active proliferative lesions were randomized to MMF with low dose steroids versus steroids alone and MMF was shown to be an effective steroid‐sparing agent but did not increase the rate of proteinuria remission at 6‐ and 12‐months .…”
Section: Response To Treatment In Iga Nephropathy In Different Ethnicmentioning
confidence: 99%
“…82 Putting these results together in a meta-analysis, it was therefore not surprising that MMF was demonstrated to be of benefit in Asians but not Caucasians. 83 In a recent study, 176 Chinese IgAN patients with active proliferative lesions were randomized to MMF with low dose steroids versus steroids alone and MMF was shown to be an effective steroid-sparing agent but did not increase the rate of proteinuria remission at 6-and 12-months. 84 All these studies are limited by small sample size and the study populations differ inherently, but these striking differences between different ethnic populations remain intriguing.…”
Section: Response To Treatment In Iga Nephropathy In Different Ethnicmentioning
confidence: 99%